Primary metabolomics and transcriptomic techniques were used to explore the regulatory mechanisms that may influence the flavor characteristics of fresh Corylus heterophylla × Corylus avellana - Lu, Minmin; Xie, Tiantian; Wang, Yaru; Yang, Jieyan; Bai, Yan; Gao, Shuang; Wu, Xiaofan; Yang, Xiuqing (Frontiers in Plant Science, 2025)
To explore the flavor related regulatory mechanisms of fresh Corylus heterophylla × Corylus avellana, a joint analysis of metabolome and transcriptome were utilized to compare the two typical C. heterophylla × C. avellana varieties with different flavors (‘yuzhui’ and ‘pingou21’) in this paper. The results showed that the genes including E2.4.1.67-1, E2.4.1.67-2, SUS-1, SUS-2, SUS-4, SUS-5, SUS-7, SUS-8, SUS-9, UGP2-2 were identified as responsible for regulating the levels of stachyose, manninotriose and raffinose in hazelnuts. CS and OGDH were deemed as the genes involved in the citric acid cycle, which was a central metabolic pathway that generated energy through the oxidation of carbohydrates, fats and proteins in hazelnuts. The genes trpD, ALDO, PK-1, PK-2, ilvH, argE-1, argE-4, argE-5, argD, PDAH, GLTI were regarded as involved in the biosynthesis of various amino acids like tryptophan, valine, alanine, and arginine. These amino acids determined the taste of C. heterophylla × C. avellana and were important precursors of other flavor-related compounds. The genes LOX2S-2, LOX2S-3, LOX2S-4 and LCAT3 were viewed as involved in the regulation of lipid biosynthesis, specifically involving 13(S)-HPODE, 9,10,13-trihome and 13(S)-HOTrE in C. heterophylla × C. avellana. These findings highlight the significance of genes and metabolites and internal regulatory mechanisms in shaping the flavor of fresh C. heterophylla × C. avellana cultivated in temperate continents. This study provides the theoretical basis for breeding excellent food functional hazelnut varieties.